2021
DOI: 10.1016/j.amsu.2021.102349
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding syndrome after radical cystoprostatectomy: A case report

Abstract: Described as a potentially lethal condition that occurs in undernourished patients, refeeding syndrome (RFD) is a severe electrolyte disturbance that includes low intracellular serum concentrations of phosphor, magnesium and potassium in patients undergoing inappropriate oral or parenteral renutrition. We report a case of RFD in a 50-year-old male patient that occurs 22 days after a radical cystoprostatectomy. The patient was anorexic after the surgery, the body mass index decreased to 12,36 kg/m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Some reports showed that the diagnosis in clinical practice is based in P-levels not in the pre-feeding period but after clinical manifestations of RS occurred. Table 3 summarizes some case reports of hospitalized patients who presented with RF [24][25][26][27][28] . The HP was the criteria used to identify the RS, and the clinical manifestations were the alert to identify the RS through the electrolyte serum levels.…”
Section: Diagnosis For Rsmentioning
confidence: 99%
“…Some reports showed that the diagnosis in clinical practice is based in P-levels not in the pre-feeding period but after clinical manifestations of RS occurred. Table 3 summarizes some case reports of hospitalized patients who presented with RF [24][25][26][27][28] . The HP was the criteria used to identify the RS, and the clinical manifestations were the alert to identify the RS through the electrolyte serum levels.…”
Section: Diagnosis For Rsmentioning
confidence: 99%